1994
DOI: 10.1021/bi00195a001
|View full text |Cite
|
Sign up to set email alerts
|

Primary Charge Separation in Photosystem I: A Two-Step Electrogenic Charge Separation Connected with P700+A0- and P700+A1- Formation

Abstract: A PS I membrane preparation from a PS II deficient mutant of Synechocystis sp. PCC 6803 (psb DI/DII/C) was investigated by picosecond photovoltage and fluorescence measurements. The photovoltage kinetics show two distinct phases. At low excitation energies the fast phase correlates with the fluorescence decay time constant of 22 +/- 4 ps. This phase is ascribed to the trapping of excitons as described by the reaction (AntiP700)* A0-->AntiP700+A0-. In addition to this phase, the photovoltage displays a second r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
42
3

Year Published

1995
1995
2008
2008

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 75 publications
(53 citation statements)
references
References 46 publications
8
42
3
Order By: Relevance
“…The solid curve in Figure 4 represents the best fit of Equations (1) and (2) for 30 ps flashes to the ps-data with the fit parameters ka = (2.5 ps) -1 and/3 = 1.0, yielding a = 4.8. Also in this preparation P-700 and P-700 + quench equally strongly (Hecks et al 1994). …”
Section: Photosystem I Membranes From Cyanobacteriamentioning
confidence: 54%
“…The solid curve in Figure 4 represents the best fit of Equations (1) and (2) for 30 ps flashes to the ps-data with the fit parameters ka = (2.5 ps) -1 and/3 = 1.0, yielding a = 4.8. Also in this preparation P-700 and P-700 + quench equally strongly (Hecks et al 1994). …”
Section: Photosystem I Membranes From Cyanobacteriamentioning
confidence: 54%
“…The present work supplements electrical measurements that are based on the light-gradient method (14,22). An early study on pea chloroplasts was restricted to the time window between 35 ps and 60 ns (the RC discharge time constant of the capacitative measuring cell).…”
Section: Discussionmentioning
confidence: 87%
“…PCC 6803, two phases were resolved in the rise of the photovoltage signal. These were assigned to the formation of the state P700+A-(22 ps) and to the further electron transfer from Ao to A1 (50 ps) (22). The lack of slower electrogenic components in ref.…”
Section: Discussionmentioning
confidence: 98%
“…They showed that, on the contrary, the relative amplitudes of the fast and slow phases were independent of the membrane potential. Leibl and co-workers (13,48) have also concluded from photovoltage measurements that the rate of electron transfer from F X Ϫ to F A /F B ( Յ50 ns) is faster than that of the slow phase of A 1 Ϫ oxidation. Both of these experimental observations thus argue against the equilibrium model and in favor of one where either the two quinones operate independently in a two-pathway model or where only one of the quinones is functional, but where there is a heterogeneity in the centers giving rise to two different rate constants for A 1 Ϫ to F X electron transfer (12).…”
Section: Resultsmentioning
confidence: 99%